"How am I going to make it through pregnancy?" A qualitative examination of prenatal maternal stress. Issue 2 (16th October 2021) - Mahaffey, Brittain L; Tilley, Jacqueline L; Molina, Lucero K; Gonzalez, Adam; Park, Elyse; Lobel, Marci
Abstract: Background: Prenatal maternal stress (PNMS) is common among childbearing women, and there is substantial evidence that persistent high levels of stress during pregnancy are associated with adverse birth outcomes and poorer postpartum mental health. Therefore, the purpose of this study was to examine the idiographic experiences of women who experienced elevated PNMS during their current or most recent pregnancy. Methods: Six focus groups were conducted, and data were collected from 26 women ( n  = 16 pregnant and n  = 10 postpartum) at a large medical center in the United States (US). Data from the semi‐structured focus group prompts were analyzed by two independent raters using conventional content analysis 21 . Results: Three key themes emerged from the data: (1) Navigating Changing Circumstances, (2) Being a "Good" Mother, and (3) Loss of Control and Autonomy. Discussion: The current study offers one of the first in‐depth examinations of the experiences of highly stressed pregnant women using a qualitative approach and identifies stressors rarely described in quantitative research. These findings suggest that women's ability to prioritize their self‐care, and receive structural/institutional supports in the workplace and instrumental support at home, and overall health literacy promote successful coping with stress and highlight important future directions for intervention.